Do it yourself: The role of early self-care ability in social skills in Japanese preschool settings. (February 2022) - Zhu, Zhu; Tanaka, Emiko; Tomisaki, Etsuko; Watanabe, Taeko; Sawada, Yuko; Li, Xiang; Jiao, Dandan; Ajmal, Ammara; Matsumoto, Munenori; Zhu, Yantong; Anme, Tokie
Self-care ability and social skills are potential areas of difficulty for preschool children. However, values about young children's self-care ability are different worldwide. This longitudinal study examined the influence of early self-care ability on social skills at the end of the preschool years. Participants were 509 children recruited from kindergartens and child care centers across Japan, whose self-care ability and social skills were assessed at baseline year and three years later (Age of children in 2015 at baseline: M  =  35 months, SD  =  6.1 months). The study found that gender was significantly associated with social skills, while preschool facility entrance age was only associated with assertion skills. After controlling gender and entrance age, early self-care ability was still positively related to later assertion and cooperation (Assertion: OR  =  2.55, 95% CI  =  1.00–6.51; Cooperation: OR  =  3.15, 95% CI  =  1.23–8.07). Implications of the findings are discussed in the context of cultural diversity, highlighting the importance of cultivating children's age-appropriate self-care ability based on daily observations and evaluations.